Uterine fibroids: a review - Arguelles-Castillo, Cinthia N.; Pérez, Juan A. Reyes; Rojas, Yazmin Urbano; Flores, Gerardo G. Montero; Menéndez, Noe A. Juárez; Oca, Luis M. Arenas Montes de; Maldonado, Tonalmitl Arzola; Paredes, David Sánchez; Navarro, Carolina Tapia; Cruz, Yoliztli Hernández; Hernández, Erick Fernando; Durán-López, Nalleli; et al. (International Surgery Journal, 2024)
Myomatosis of large elements are benign tumors resulting from the growth of muscular and fibrous tissue, which can be embedded or adhered to the uterine wall and their classification varies between submucosal, intramural or subserous depending on the depth they reach. More frequently, symptomatic patients report the presence of abundant abnormal uterine bleeding, dysmenorrhea, dyspareunia and infertility. This pathology represents 40-60% of all hysterectomies, of the total, 30% in women of childbearing age. Different possible triggers of uterine fibroids have been described, which is why it is considered to be of multifactorial origin. Ultrasound is usually used frequently due to its high availability and low cost, this being the first diagnostic image of choice and the gold standard, through transvaginal ultrasound. The management of myomastomas entails a great social problem, since therapy seeks treatment methods that prevent the recurrence of the disease, and in case of satisfied parity, hysterectomy is the ideal option, but in those patients still of fertile age and with desire of pregnancy, less drastic procedures such as myomectomy will be carried out. Finally, some post-surgical complications have been discussed, among which the generation of adhesions due to the scarring resulting from the surgical intervention was described, which could generate infertility or greater difficulty in conceiving.